Downregulation of GNA15 Inhibits Cell Proliferation via P38 MAPK Pathway and Correlates with Prognosis of Adult Acute Myeloid Leukemia With Normal Karyotype - Li, Mengya; Liu, Yu; Liu, Yajun; Yang, Lu; Xu, Yan; Wang, Weiqiong; Jiang, Zhongxing; Liu, Yanfang; Wang, Shujuan; Wang, Chong (Frontiers in Oncology, 2021)
Background: AML with a normal karyotype is highly heterogonous, and the current risk stratification is still insufficient to differentiate patients from high-risk to standard-risk. Changes in some genetic profiles may contribute to the poor prognosis of AML. Although the prognostic value of GNA15 in AML has been reported based on the GEO database, the prognostic significance of GNA15 has not been verified in clinical samples. The biological functions of GNA15 in AML development remain open to investigation. This study explored the clinical significance, biological effects and molecular mechanism of GNA15 in AML. Methods: RT-qPCR was used to detect the mRNA expression level of GNA15 in blasts of bone marrow specimens from 154 newly diagnosed adult AML patients and 26 healthy volunteers. AML cell lines, Kasumi-1 and SKNO-1, were used for lentiviral transfection. CCK8 and colony formation assays were used to determine cell proliferation. Cell cycle and apoptosis were analyzed by flow cytometry. The relevant signaling pathways were evaluated by Western blot. The Log-Rank test and Kaplan-Meier were used to evaluate survival rate, and the Cox regression model was used to analyze multivariate analysis. Xenograft tumor mouse model was used for in vivo experiments. Results: The expression of GNA15 in adult AML was significantly higher than that in healthy individuals. Subjects with high GNA15 expression showed lower overall survival and relapse-free survival in adult AML with normal karyotype. High GNA15 expression was independently correlated with a worse prognosis in multivariate analysis. Knockdown of GNA15 inhibited cell proliferation and cell cycle progression, and induced cell apoptosis in AML cells. GNA15-knockdown induced down-regulation of p-P38 MAPK and its downstream p-MAPKAPK2 and p-CREB. Rescue assays confirmed that P38 MAPK signaling pathway was involved in the inhibition of proliferation mediated by GNA15 knockdown. Conclusions: In summary, GNA15 was highly expressed in adult AML, and high GNA15 expression was independently correlated with a worse prognosis in adult AML with normal karyotype. Knockdown of GNA15 inhibited the proliferation of AML regulated by the P38 MAPK signaling pathway. Therefore, GNA15 may serve as a potential prognostic marker and a therapeutic target for AML in the future.